Calidad del sueño y parálisis del sueño en estudiantes de la carrera de Odontología de la Universidad Nacional de Loja - Valencia Amay, Karen Michelle (2022)
A good quality of sleep encompasses a good night’s sleep and maintain good daytime operation, whereas, sleep paralysis is a disorder characterized by the inability to move during sleep accompanied by hallucinations. This quantitative, descriptive and cross-sectional study was developed with the objective of determining the quality of sleep and the presentation of sleep paralysis, where 154 students of the UNL Dentistry career participated, of which 55.84% (n =86) are in the age range of 21-25 years, 77.3% (n=119) belong to the female sex, most are single, 52% (n=80) come from urban areas, 87% (n=134) dedicate themselves to study and 13% (n=20) study and work. 79.8% (n=123) are poor sleepers and 20.1% (n=31) are good sleepers. 34% (n=53) presented at least one episode of sleep paralysis, 86.8% (n=46) corresponded to women and 13.2% (n=7) to men, 54.7% ( n=29 women) presented the episode upon awakening, and 9.4%(n=5 men) early in the dream, 49.1% (n=26 women) had a duration of seconds and 7.5% (n=4 men) of few minutes, 62.3% (n=33 women) and 5.7% (n=3 men) is associated with anxiety or fear, 1.9% (n=1) is diagnosed with sleep disorder, 26.4% (n=14 women) and 3.8% (n=2 men) presented hallucinations, predominantly visual ones. No statistically significant relationship was found between sleep quality and sleep paralysis that is affecting the quality of life of students